External financing of cooperatives in Spain - Vargas Vasserot, Carlos (Cooperativismo & Desarrollo, 2025)
The economic crises highlight the excessive dependence of Spanish companies on credit and bank financing. This dependence, both for their current operations and for their investment needs, is even more pronounced in the case of smaller companies. Furthermore, the cooperative model presents some financial limitations, among which is the existence of a high percentage of members who avoid increasing their investment. Spanish cooperative legislation (which consists of a state law and 17 regional laws, as well as other sectoral laws, referring to microcooperatives, credit unions, etc.) regulates various external financing instruments that attempt to combine the need for third-party capital investment with ensuring that the control and management of the company remains with the entity’s members. This paper aims to analyze the regulation of the alternative financing instruments available to Spanish cooperatives and their effective use in practice, which, as we will see, is scarce.